Local preferences and the allocation of attention in equity-based crowdfunding - Marco Bade; Martin Walther (Review of Managerial Science, 2021)
This study examines drivers of investment probability in equity-based crowdfunding using a hand-collected and comprehensive data set from a well-established platform. The analysis confirms several effects that have been reported in the recent literature on other crowdfunding markets. Extending recent research, we study moderators of local preferences of investors. Novel to the literature, we find that (1) local preferences are more pronounced in campaigns of younger ventures, (2) herding-like behaviour is stronger in local campaigns and (3) local investors are more responsive to updates posted by entrepreneurs, compared to non-locals. Our results suggest that investors allocate more attention to campaigns for which they have information advantages, such as local campaigns, due to their limited capacity to process information. Such behaviour may eventually amplify information asymmetry and local preferences. Our findings have practical implications for entrepreneurs, investors and platforms.
Keywords: D83; G11; L26; M13; 650; Individual investor behaviour; Local preferences; Attention allocation; Limited information processing capacity; Equity-based crowdfunding